Psychological Impact on Victims of Domestic Violence in Sawahlunto City - Sabrina Sabilla; Dani Yoselisa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study is motivated by the prevalence of domestic violence (DV) cases in Sawahlunto City, which have a significant impact on the psychological condition of the victims. The main objective of this research is to describe the psychological impacts experienced by DV victims and to identify the contributing factors behind the occurrence of such violence. A qualitative approach with a phenomenological method was employed to gain an in-depth understanding of the victims’ subjective experiences. The research subjects consisted of four DV victims as primary informants and one neighbor as a supporting informant. Data were collected through in-depth interviews and analyzed using data reduction, data display, and conclusion drawing. The validity of the data was tested through source and method triangulation. The findings reveal that DV victims in Sawahlunto experience psychological impacts in three main aspects. First, the cognitive aspect, manifested in negative self-perceptions, decreased decision-making ability, normalization of violence, and concentration difficulties due to trauma and low self-efficacy. Second, the affective aspect, characterized by prolonged negative emotions such as fear, anxiety, depression, guilt, shame, and suppressed anger. Third, the conative aspect, marked by social withdrawal, resignation, difficulties in planning the future, and ambivalence to leave abusive relationships due to fear, stigma, economic dependency, and trauma. This study emphasizes that the psychological impacts of DV not only damage the victims’ mental health but also hinder their recovery process. The findings are expected to serve as a foundation for psychological assistance programs and the formulation of domestic violence handling policies at the local level, particularly in Sawahlunto City.